Case Reports: Management Challenges in Pediatric Germ Cell Tumors - Carr, Sophie; Safavi, Arash; Skarsgard, Erik D. (Frontiers in Pediatrics, 2021)
Germ cell tumors in infants are most frequently extragonadal, benign and amenable to surgical resection. An unusual feature of germ cell tumors is the potential coexistence of malignant with benign disease which makes it possible for patients with an incompletely resected tumors to experience either a benign or malignant recurrence. A challenge to postoperative surveillance is the interpretation of serum alpha fetoprotein (AFP), a marker of malignancy, that is physiologically elevated during the first year of life. A rare subset of germ cell tumors occur in the retroperitoneum. Although the vast majority are benign, these tumors are often large and distort normal anatomy, and may demonstrate local invasiveness that increase risk of resection. The intent of these reports is to caution readers about these unusual features of germ cell tumors of infancy.